Validação das regras de Ottawa para a população Portuguesa: estudo prospectivo. - Rodrigues, Patricia; Rosa, Isabel; Campagnolo, João Lameiras (Acta Médica Portuguesa, 2011)
Acute ankle injury is one of the main reasons for observation of patients in the emergency department. Only 15% present with clinically significant fractures, but they are almost always referred for radiography. The Ottawa ankle rules have provided specific directions for carrying out radiography in these situations, allowing a reduction in hospital costs and reducing exposure to ionizing radiation. The aim of the study is to verify that the protocol of the Ottawa rules for evaluating ankle trauma can adapt to a sample of the Portuguese population.This prospective study was done in the Emergency Department of Orthopedics, for a period of 9 months, integrating all patients who presented with complaints in the ankle with less than 48 hours development. All patients underwent radiography of the injured area. Radiographic images were evaluated by the orthopaedic doctor in the emergency department. Patients were reassessed in about 10-15 days after injury by the same observer.We evaluated 123 patients. The average age was 35.2 (range, 7 to 88) years. Sixty had positive criteria for radiological assessment, of which 43 had fracture; none of the patients with negative criteria had fratures. Sensitivity of Ottawa ankle rules for detecting fractures was 100%.The implementation of the Ottawa ankle rules appears to have potential to reduce the number of radiographs for the assessment of these patients by about 51%. The results of this study demonstrate no false negatives and are consistent with the results of other similar studies which sensitizes us to implement these criteria in our emergency services.